Encyclopedia of industrial biotechnology : bioprocess, bioseparation, and cell technology - Flickinger, Michael C. (Wiley, 2010)
"A new up-to-date resource for the global biotechnology industry. It is based on the Encyclopedia of Bioprocess Technology (Flickinger and Drew, 1999) and the Encyclopedia of Cell Technology (Spier, 2000). The content was fully revised, updated, and expanded to present all key aspects - theoretical and practical - of industrial biological processes, techniques, equipment, products, as well as ethical and regulatory issues. The focus has been expanded to include additional important areas such as: regulatory guidelines (U.S. and international), GMP facilities design, manufacturing methods for biopharmaceuticals, biofabrication, tissue engineering, bioelectronic devices, bionanotechnology."--Publisher description.